2020
DOI: 10.1002/jsfa.10321
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation with Chlorella vulgaris, Chlorella protothecoides, and Schizochytrium sp. increases propionate‐producing bacteria in in vitro human gut fermentation

Abstract: BACKGROUND Gut microbiota are major contributors to host metabolism and are considered as potential targets of novel therapeutics. Microalgae have a strong potential for use as prebiotics because they are a rich source of proteins, fatty acids, fiber, and minerals for nutritional supplementation in humans. Nevertheless, there has been insufficient research into the effect of microalgae on gut microbiota. To investigate the effects of three edible microalgae (Chlorella vulgaris, Chlorella protothecoides, and Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 36 publications
2
10
1
Order By: Relevance
“…Microbiome results suggest that the use of C. vulgaris in piglet feeding, in combination or not with enzymes, significantly affects the faecal bacterial structure of piglets, as previously observed in humans 14 . In addition, C. vulgaris incorporation supplemented with 0.005% Rovabio increased the relative abundance of Lactobacillus and Oscillospira .…”
Section: Discussionsupporting
confidence: 68%
“…Microbiome results suggest that the use of C. vulgaris in piglet feeding, in combination or not with enzymes, significantly affects the faecal bacterial structure of piglets, as previously observed in humans 14 . In addition, C. vulgaris incorporation supplemented with 0.005% Rovabio increased the relative abundance of Lactobacillus and Oscillospira .…”
Section: Discussionsupporting
confidence: 68%
“…We selected these four species because they currently represent the microalgae of greatest interest in the food and feed sector [ 8 , 13 ]. We hypothesized that composition and metabolism of canine fecal microbiota would be influenced by microalgae supplementation; particularly, we expected an increase concentration of the three major SCFA (acetate, propionate and butyrate), in accordance with previously in vitro cited studies [ 31 , 32 ], and higher concentration of microbial species known to be SCFA producers (i.e., Ruminococcaceae, Clostridium cluster XIV, Turicibacter spp., C. leptum, C. coccoides) [ 37 ]; in addition, we assumed that microbial species thought to have undesired influences on canine gut health would decrease. Lastly, we hypothesized a decrease of metabolites deriving from bacterial proteolysis (ammonia, BCFA, biogenic amines) due to the enhanced saccharolytic activities of bacterial populations.…”
Section: Introductionsupporting
confidence: 75%
“…Microalgae biomass showed a selective stimulation of beneficial microorganisms and inhibition of undesired bacteria on colonic microbiota. A previous study conducted by Jin et al [ 32 ] reported that supplementation with Chlorella vulgaris and other microalgae increased propionate-producing bacteria in an in vitro human gut fermentation model. According to the previously cited studies, in order to evaluate the effects of microalgae on intestinal microbiota, it is appropriate to use an in vitro digestion procedure and subsequently undergo the digested biomass to colonic in vitro fermentation, with the aim to examine the potential microbiota modulation activities of microalgae [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other authors also used this protocol to study the modulatory effect of polyphenols and sesquiterpene lactones from artichoke heads 22 or Chlorella spp. 23 on gut microbiota composition and functionality.…”
Section: Development Of the Protocolmentioning
confidence: 99%